Psalms of wonder poems from the book of songs - Wallace, Carey 1974-; Le, Khoa 1982- (Louisville, KY Presbyterian Publishing Corporation, 2023)
For readers of all ages, these inviting poems and gorgeous illustrations inspired by the book of Psalms echo all its wonder and courage, comfort and joy, protection and love.
Wallace_Interior-1 -- Wallace_Interior-2 -- Wallace_Interior-3 -- Wallace_Interior-4 -- Wallace_Interior-5 -- Wallace_Interior-6 -- Wallace_Interior-7 -- Wallace_Interior-8 -- Wallace_Interior-9 -- Wallace_Interior-10 -- Wallace_Interior-11 -- Wallace_Interior-12 -- Wallace_Interior-13 -- Wallace_Interior-14 -- Wallace_Interior-15 -- Wallace_Interior-16 -- Wallace_Interior-17 -- Wallace_Interior-18 -- Wallace_Interior-19 -- Wallace_Interior-20 -- Wallace_Interior-21 -- Wallace_Interior-22 -- Wallace_Interior-23 -- Wallace_Interior-24 -- Wallace_Interior-25 -- Wallace_Interior-26 -- Wallace_Interior-27 -- Wallace_Interior-28 -- Wallace_Interior-29 -- Wallace_Interior-30 -- Wallace_Interior-31 -- Wallace_Interior-32 -- Wallace_Interior-33 -- Wallace_Interior-34 -- Wallace_Interior-35 -- Wallace_Interior-36 -- Wallace_Interior-37 -- Wallace_Interior-38 -- Wallace_Interior-39 -- Wallace_Interior-40 -- Wallace_Interior-41 -- Wallace_Interior-42 -- Wallace_Interior-43 -- Wallace_Interior-44 -- Wallace_Interior-45 -- Wallace_Interior-46 -- Wallace_Interior-47 -- Wallace_Interior-48 -- Wallace_Interior-49 -- Wallace_Interior-50 -- Wallace_Interior-51 -- Wallace_Interior-52 -- Wallace_Interior-53 -- Wallace_Interior-54 -- Wallace_Interior-55 -- Wallace_Interior-56 -- Wallace_Interior-57 -- Wallace_Interior-58 -- Wallace_Interior-59 -- Wallace_Interior-60 -- Wallace_Interior-61 -- Wallace_Interior-62 -- Wallace_Interior-63 -- Wallace_Interior-64.
Original poems and artwork inspired by the book of Psalms echo its themes of wonder, courage, comfort, joy, protection, and love
Description based on publisher supplied metadata and other sources
Keywords: Bible -- Poetry; Religious poetry, American; Children's poetry, American; American poetry; Psalms